Danos de Dichelops melacanthus (dallas, 1851) e Euschistus heros (Fabricius, 1798) (Heteroptera: pentatomidae), em plântulas e o impacto no desenvolvimento da soja, com tratamentos de sementes - Silva , João Cezar Alves da (2020)
Soybean is a highly important commodity for Brazilian agribusiness, but the national average productivity can be increased considerably, since the productive potential of the crop is greater than 8,000 kg ha-1 (CONAB, 2017). There are several factors that can cause productive losses in soybeans, such as unfavorable edaphoclimatic conditions, diseases and pests. Some new challenges arise and need to be studied, such as the potential for damage caused by Dichelops melacanthus (Dallas, 1851) and by Euschistus heros (Fabricius, 1798) in soybean plantlets and the efficiency of seed treatments in controlling these insects. Thus, the purpose of this study was to evaluate damages of D. melacanthus and E. heros in cotyledons, in the initial development and in the production of soybean plants with different seed treatments. This study was performed in randomized blocks in a 5X5 factorial arrangement, with five blocks, in a semi-climatic greenhouse. The insect combinations were 4th instar nymphs and adults of D. melacanthus and E. heros and control (without insects). The seed treatments were Imidacloprid+Tiodicarb in the form of industrial seed treatment, Imidacloprid+Tiodicarb on farm, Tiametoxam on farm, Fipronil+Pyraclostrobin+Methyl Thiophanate on farm and control (without insecticide). The study was performed in duplicate, one part to proceed with the destructive analysis and the other part to evaluate the production components. The destructive evaluations were dry root weight, dry weight of stem and petioles, dry weight of cotyledons and dry weight of leaves, performed at 20 days after emergence. The evaluations of the production components were plant height at harvest, basal diameter at harvest, mass of one thousand grains, mass of grains per plant, total number of pods per plant and total number of grains per plant. It was observed that nymphs and adults of E. heros did not cause a reduction in the variables evaluated due to their feeding on plantlets, when compared to the control treatment. On the other hand, the results show that D. melacanthus nymphs and adults negatively affected the root dry mass and leaf dry matter and adults of this species caused a reduction in dry mass of stem and petiole due to their feeding process. Only the dry leaf mass variable was affected by seed treatments. The cotyledon fall speed index did not show responses for either the insect factor or the insecticide factor, and the stinkbugs death speed index showed significant differences between treatments for both factors. Grain production and production components were not affected by the damage that occurred in the initial development phase. It is concluded that D. melacanthus has the potential to cause damage to structures in the early development of soybean crop and the seed treatments used showed effect on the mortality of nymphs and adults of E. heros and D. melacanthus in soybean plantlets. However, considering that the damage to the soybean plantlets did not cause a reduction in the final production, the seed treatment is not recommended for the management of these stinkbugs at the beginning of the development of the soybean culture.